Fundamentals of Astrophysical Fluid Dynamics : Hydrodynamics, Magnetohydrodynamics, and Radiation Hydrodynamics /: Hydrodynamics, Magnetohydrodynamics, and Radiation Hydrodynamics. (2020) - Kato, Shoji; Fukue, Jun
No abstract available